Method for preparing tungsten-high-entropy alloy micro-laminated composite material based on flaky powder
By preparing tungsten-high entropy alloy micro-laminated composite materials based on sheet powder, the problem of difficulty in realizing micro-scale soft-hard laminated arrangement in the prior art is solved, and the high impact resistance and toughness of the material are improved.
Patent Information
- Application Number
- CN202510098867.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-18
AI Technical Summary
The existing methods are difficult to achieve the microscopic soft-hard-phase stacking arrangement required for imitating shell structures, resulting in the failure of material performance to fully utilize.
Using a sheet-shaped powder-based method, the tungsten powder and high-entropy alloy powder were prepared into sheet-layer powder by plasma ball milling, and mixed in a V-type mixer, followed by cold-pressing molding in a cold pressing mold, and finally hot-pressing sintering in a vacuum hot pressing furnace to prepare a tungsten-high-entropy alloy micro-laminated composite material.
Through the material structure design of the "soft-hard" alternating overlapping of the mother-of-pearl layer of imitation shell shells, the impact resistance of the material is improved, the matching limit of the strength-ductility of the refractory metal is broken, and its toughness is improved without reducing the strength of the composite material.
Smart Images

Figure CN119839296A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder. Background Art With the continuous development of weapons and equipment under modern high-tech conditions and the changes in battlefield environment, the performance requirements of armor protection materials are increasing. New armor materials not only need to adapt to the harsh battlefield environment, but also need to improve mobility while ensuring the protective effect. They are required to have high impact resistance, low cost and lightweight characteristics. Laminated composite armor is currently the most widely used type of armor material because of its relatively simple structure and easy large-scale production. The micro-laminated structure derived from the mother-of-pearl layer of shells is achieved by alternating two or more materials with different physical and chemical properties according to a certain rule. Compared with traditional single materials, in addition to the excellent properties of different materials, a large number of micro-laminated interfaces can quickly consume impact energy, deflect cracks, and improve the anti-penetration ability of armor materials. Therefore, how to effectively construct a micro-laminated structure has become a major challenge in current research.
[0002] Existing lamination methods such as hot rolling and stacked rolling can obtain layered composite materials, but the layered structures obtained by these methods are usually at a macroscopic scale, and it is difficult to achieve the microscopic scale soft-hard phase stacking arrangement required for the shell-like structure, resulting in the failure to fully utilize the material properties. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder, which solves the problem that the layered composite material prepared by the existing method is usually macroscopic in structure and difficult to achieve the microscopic scale required for the shell-like structure.
[0004] The technical solution adopted by the present invention is a method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder, which is specifically implemented according to the following steps: Step 1, plasma ball milling tungsten powder and high entropy alloy powder respectively to obtain tungsten flake powder and high entropy alloy flake powder; Step 2, mixing the tungsten flaky powder and the high entropy alloy flaky powder obtained in step 1 in a V-type mixer to obtain a tungsten-high entropy alloy co-flaky mixed powder; Step 3, placing the tungsten-high entropy alloy co-laminated mixed powder obtained in step 2 into a steel cold pressing mold for self-assembly, and then cold pressing to obtain a tungsten-high entropy alloy co-laminated cold pressed green body; Step 4, hot pressing and sintering the tungsten-high entropy alloy co-laminated cold-pressed green body obtained in step 3 in a vacuum hot pressing furnace to obtain a tungsten-high entropy alloy micro-laminated composite material. The present invention is also characterized in that: In step 1, the average particle size of the tungsten powder is 1 μm to 50 μm, and the average particle size of the high entropy alloy powder is 10 μm to 50 μm.
[0005] The specific process of step 1 is: tungsten powder and high entropy alloy powder are respectively loaded into a stainless steel ball mill for ball milling. Before ball milling, the stainless steel ball mill is first evacuated and then filled with argon. The evacuation and argon filling operations are repeated three times to obtain tungsten flake powder and high entropy alloy flake powder.
[0006] The ball-to-material ratio is 10~50:1, the ball mill speed is 900r / min~1400r / min, and the ball mill time is 1h~4h.
[0007] During the ball milling process, the discharge current was 80 mA, the discharge voltage was 20 kV, and the discharge frequency was 7 kHz ~ 9 kHz.
[0008] The diameter-to-thickness ratios of the tungsten flake powder and the high entropy alloy flake powder are both ≥50.
[0009] In step 2, the ball-to-material ratio during the mixing process is 1:10, the rotation speed is 100 r / min~200 r / min, and the ball milling time is 1h~4h.
[0010] In step 2, the mass percentage of the tungsten lamellar powder is 50% to 90%, the mass percentage of the high entropy alloy lamellar powder is 10% to 50%, and the sum of the mass percentages of the two is 100%.
[0011] In step 3, the cold pressing pressure is 15MP~25MPa, and the holding time is 30s~90s.
[0012] In step 4, the hot pressing sintering temperature is 1000°C to 1400°C, the holding time is 20min to 60min, the pressure is 30MPa to 60MPa, and the vacuum degree is not greater than 10 -1 Pa.
[0013] The beneficial effects of the present invention are as follows: based on the physical properties of refractory metal W such as high melting point, high hardness and high strength, the method of the present invention introduces a two-phase AlFeCoNi system or a lightweight high entropy alloy for the purpose of toughening, and utilizes the advantages of high entropy alloy such as low density and matching strength and toughness to combine tungsten with the high entropy alloy, thereby improving its toughness without reducing the strength of the composite material, breaking through the matching limit of the strength-ductility of the refractory metal tungsten, and using the material structure design concept of alternating "soft-hard" phases of imitation shell mother-of-pearl layers, and utilizing the configuration design of the multi-interface of the laminated structure to improve the impact resistance of the material, and prepare a tungsten-high entropy alloy micro-laminated composite material with a bionic micro-laminated structure; at the same time, using plasma ball milling to combine traditional ball milling technology with dielectric barrier discharge plasma, effectively activate metal powder to shorten the preparation time, and can use the rapid heating generated by plasma and the synergistic effect of high-energy electron bombardment to improve the ductility of metal tungsten or high entropy alloy, promote the deformation of metal powder, and provide a rapid preparation method for flaky powder construction. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 is a flow chart of the method of the present invention; Figure 2 This is a microstructure diagram of the tungsten-high entropy alloy micro-laminated composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0014] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0015] The present invention provides a method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder, such as Figure 1 As shown, the specific implementation steps are as follows: Step 1, plasma ball milling tungsten powder and high entropy alloy powder respectively to obtain tungsten flake powder and high entropy alloy flake powder; The specific process is as follows: tungsten powder with an average particle size of 1μm~50μm and high entropy alloy powder with an average particle size of 10μm~50μm are respectively loaded into a stainless steel ball mill and ball milled at a speed of 900r / min~1400r / min for 1h~4h, and the ball-to-material ratio is 10~50:1. Before ball milling, the stainless steel ball mill is first evacuated and then filled with argon. The evacuation and argon filling operations are repeated three times to obtain tungsten flake powder and high entropy alloy flake powder. The diameter-to-thickness ratio of the tungsten flake powder and the high entropy alloy flake powder is ≥50; Among them, the discharge current during the ball milling process is 80mA, the discharge voltage is 20 kV, and the discharge frequency is 7kHz~9kHz; Among them, the high entropy alloy powder adopts a dual-phase structure such as AlFeCoNi system or other light high entropy alloy powder; Step 2, using the tungsten flaky powder and the high entropy alloy flaky powder obtained in step 1 as raw material powders, mixing them in a V-type mixer at a speed of 100 r / min to 200 r / min for 1 h to 4 h to obtain a tungsten-high entropy alloy co-flaky mixed powder; Among them, the mass percentage of tungsten flake powder is 50%~90%, the mass percentage of high entropy alloy flake powder is 10%~50%, and the sum of the mass percentages of the two is 100%; Stainless steel grinding balls are added to the V-type mixer, and the ball-to-material ratio is 1:10; Step 3, the tungsten-high entropy alloy co-laminated mixed powder obtained in step 2 is loaded into a steel cold pressing mold for self-assembly, and then cold pressed for 30s to 90s at a pressure of 15MP to 25MPa on a four-column hydraulic press to obtain a tungsten-high entropy alloy co-laminated cold pressed green body; Step 4: cold-press the tungsten-high entropy alloy green sheet obtained in step 3 under a vacuum of no more than 10 -1 Pa vacuum hot pressing furnace at a heating rate of 100°C / min to 1000°C~1400°C and sintering for 20min~60min. The pressing pressure during the sintering process is 30MPa~60MPa. The furnace is cooled to obtain a tungsten-high entropy alloy micro-laminated composite material.
[0016] The method of the present invention is based on the excellent performance of strength-toughness matching of the "brick-mud" structure of the soft and hard phases of the shell mother-of-pearl layer alternately stacked, and proposes a structural design concept for shell-like tungsten-high entropy alloy micro-laminated composite materials, forming a technical method for preparing tungsten-high entropy alloy micro-laminated composite materials, providing a new material system and technical support for the development of lightweight, high-strength, high-toughness, and more excellent impact resistance armor protection materials.
[0017] Example 1 Step 1: prepare a dual-phase high entropy alloy powder Al with an average particle size of 8 μm and an average particle size of 40 μm. 19 Fe 20 Co 20 Ni 41 The tungsten and Al2O3 flake powders were obtained by ball milling at a speed of 1200 r / min for 2 h. The ball-to-material ratio was 40:1. The stainless steel ball mill was evacuated and filled with argon before ball milling. The evacuation and filling with argon were repeated three times to obtain tungsten flake powder and Al2O3 flake powder. 19 Fe 20 Co 20 Ni 41 The diameter to thickness ratio of the flake powder, tungsten flake powder and high entropy alloy flake powder is ≥50; Among them, the discharge current during ball milling was 80 mA, the discharge voltage was 20 kV, and the discharge frequency was 8 kHz; Step 2: Mix the tungsten flake powder obtained in step 1 with Al 19 Fe 20 Co 20 Ni 41 The flake powder was used as the raw material powder and mixed in a V-type mixer at a speed of 200 r / min for 2 h to obtain tungsten-Al 19 Fe 20 Co 20 Ni 41 Co-laminated mixed powder; Among them, the mass percentage of tungsten flake powder is 80%, Al 19 Fe 20 Co 20 Ni 41 The mass percentage of the flake powder is 20%; Stainless steel grinding balls are added to the V-type mixer, and the ball-to-material ratio is 1:10; Step 3: The tungsten-high entropy alloy co-laminated mixed powder obtained in step 2 is placed in a steel cold pressing mold for self-assembly, and then cold pressed for 60 seconds at a pressure of 20 MPa on a four-column hydraulic press to obtain a tungsten-Al 19 Fe 20 Co 20 Ni 41 Cold pressing of green body with common laminae; Step 4: The tungsten-Al 19 Fe 20 Co 20 Ni 41 The green body is cold pressed in a vacuum degree of no more than 10 -1 Pa vacuum hot pressing furnace at a heating rate of 100 ° C / min to 1100 ° C sintering for 40 minutes, the pressing pressure during the sintering process is 30 MPa, and the furnace is cooled to obtain tungsten-Al 19 Fe 20 Co 20 Ni 41 Micro-laminated composites.
[0018] Example 2 Step 1: prepare a dual-phase high entropy alloy powder Al with an average particle size of 8 μm and an average particle size of 40 μm. 19 Fe 20 Co 20 Ni 41 The tungsten flake powder and Al2O3 powder were respectively put into a stainless steel ball mill and ball milled at a speed of 1300 r / min for 1 h, with a ball-to-material ratio of 50:1. Before ball milling, the stainless steel ball mill was first evacuated and then filled with argon. The evacuation and argon filling operation were repeated three times to obtain tungsten flake powder and Al2O3 powder. 19 Fe 20 Co 20 Ni41 The diameter to thickness ratio of the flake powder, tungsten flake powder and high entropy alloy flake powder is ≥50; Among them, the discharge current during ball milling was 80 mA, the discharge voltage was 20 kV, and the discharge frequency was 8 kHz; Step 2: Mix the tungsten flake powder obtained in step 1 with Al 19 Fe 20 Co 20 Ni 41 The flake powder was used as the raw material powder and mixed in a V-type mixer at a speed of 200 r / min for 2 h to obtain tungsten-Al 19 Fe 20 Co 20 Ni 41 Co-laminated mixed powder; Among them, the mass percentage of tungsten flake powder is 90%, Al 19 Fe 20 Co 20 Ni 41 The mass percentage of the flake powder is 10%; Stainless steel grinding balls are added to the V-type mixer, and the ball-to-material ratio is 1:10; Step 3: The tungsten-high entropy alloy co-laminated mixed powder obtained in step 2 is placed in a steel cold pressing mold for self-assembly, and then cold pressed on a four-column hydraulic press at a pressure of 25 MPa for 40 seconds to obtain a tungsten-Al 19 Fe 20 Co 20 Ni 41 Cold pressing of green body with common laminae; Step 4: The tungsten-Al 19 Fe 20 Co 20 Ni 41 The green body is cold pressed in a vacuum degree of no more than 10 -1 Pa vacuum hot pressing furnace at a heating rate of 100 ° C / min to 1200 ° C sintering for 60 min, the pressing pressure during the sintering process is 30 MPa, and the furnace is cooled to obtain tungsten-Al 19 Fe 20 Co 20 Ni 41 Micro-laminated composites.
[0019] Example 3 Step 1: mix tungsten powder with an average particle size of 10 μm and dual-phase high entropy alloy powder Al with an average particle size of 40 μm. 19 Fe 20 Co 20 Ni 41The tungsten and Al2O3 flake powders were obtained by ball milling at a speed of 1400 r / min for 1 h, with a ball-to-material ratio of 30:1. The stainless steel ball mill was evacuated and then filled with argon before ball milling. The evacuation and argon filling operations were repeated three times to obtain tungsten flake powder and Al2O3 flake powder. 19 Fe 20 Co 20 Ni 41 The diameter to thickness ratio of the flake powder, tungsten flake powder and high entropy alloy flake powder is ≥50; The discharge current during ball milling is 80 mA, the discharge voltage is 20 kV, and the discharge frequency is 9 kHz. Step 2: The tungsten flake powder obtained in step 1 and Al 19 Fe 20 Co 20 Ni 41 The flake powder was used as the raw material powder and mixed in a V-type mixer at a speed of 200 r / min for 2 h to obtain tungsten-Al 19 Fe 20 Co 20 Ni 41 Co-laminated mixed powder; Among them, the mass percentage of tungsten flake powder is 70%, Al 19 Fe 20 Co 20 Ni 41 The mass percentage of the flake powder is 30%; Stainless steel grinding balls are added to the V-type mixer, and the ball-to-material ratio is 1:10; Step 3: The tungsten-high entropy alloy co-laminated mixed powder obtained in step 2 is placed in a steel cold pressing mold for self-assembly, and then cold pressed on a four-column hydraulic press at a pressure of 15 MPa for 90 seconds to obtain a tungsten-Al 19 Fe 20 Co 20 Ni 41 Cold pressing of green body with common laminae; Step 4: The tungsten-Al 19 Fe 20 Co 20 Ni 41 The green body is cold pressed in a vacuum degree of no more than 10 -1 Pa vacuum hot pressing furnace at a heating rate of 100 ° C / min to 1300 ° C sintering for 60 min, the pressing pressure during the sintering process is 60 MPa, and the furnace is cooled to obtain tungsten-Al 19 Fe 20 Co 20 Ni 41 Micro-laminated composites.
[0020] Example 4 Step 1: tungsten powder with an average particle size of 10 μm and dual-phase high entropy alloy powder FeCoNiCrAl 0.6 The tungsten flake powder and FeCoNiCrAl2O3 powder were respectively put into a stainless steel ball mill and ball milled at a speed of 1300 r / min for 1 h, with a ball-to-material ratio of 40:1. Before ball milling, the stainless steel ball mill was first evacuated and then filled with argon. The evacuation and argon filling operation were repeated three times to obtain tungsten flake powder and FeCoNiCrAl2O3 powder. 0.6 The diameter to thickness ratio of the flake powder, tungsten flake powder and high entropy alloy flake powder is ≥50; Among them, the discharge current during ball milling was 80 mA, the discharge voltage was 20 kV, and the discharge frequency was 7 kHz; Step 2: Mix the tungsten flake powder obtained in step 1 with FeCoNiCrAl 0.6 The flake powder was used as raw material powder and mixed in a V-type mixer at a speed of 200 r / min for 2 h to obtain tungsten-FeCoNiCrAl 0.6 Co-laminated mixed powder; Among them, the mass percentage of tungsten flake powder is 60%, Al 19 Fe 20 Co 20 Ni 41 The mass percentage of the flake powder is 40%; Stainless steel grinding balls are added to the V-type mixer, and the ball-to-material ratio is 1:10; Step 3: The tungsten-high entropy alloy co-laminated mixed powder obtained in step 2 is placed in a steel cold pressing mold for self-assembly, and then cold pressed for 60 seconds at a pressure of 20 MPa on a four-column hydraulic press to obtain tungsten-FeCoNiCrAl 0.6 Cold pressing of green body with common laminae; Step 4: The tungsten-FeCoNiCrAl 0.6 The green body is cold pressed in a vacuum degree of no more than 10 -1 Pa vacuum hot pressing furnace at a heating rate of 100 ° C / min to 1100 ° C sintering for 40 minutes, the pressing pressure during the sintering process is 30 MPa, and the furnace is cooled to obtain tungsten-FeCoNiCrAl 0.6 Micro-laminated composites.
[0021] Example 5 Step 1, tungsten powder with an average particle size of 20 μm and dual-phase high entropy alloy powder AlNbTiV with an average particle size of 25 μm are respectively placed in a stainless steel ball mill and ball milled at a speed of 1200 r / min for 2 hours, with a ball-to-material ratio of 50:1. Before ball milling, the stainless steel ball mill is first evacuated and then filled with argon. The vacuuming and argon filling operations are repeated three times to obtain tungsten flake powder and AlNbTiV flake powder, and the diameter to thickness ratio of the tungsten flake powder and the high entropy alloy flake powder are both ≥50; Among them, the discharge current during ball milling was 80 mA, the discharge voltage was 20 kV, and the discharge frequency was 9 kHz; Step 2, using the tungsten flaky powder and AlNbTiV flaky powder obtained in step 1 as raw material powders, mixing them in a V-type mixer at a speed of 200 r / min for 2 hours to obtain a tungsten-AlNbTiV co-flaky mixed powder; Among them, the mass percentage of tungsten flake powder is 50%, Al 19 Fe 20 Co 20 Ni 41 The mass percentage of the flake powder is 50%; Stainless steel grinding balls are added to the V-type mixer, and the ball-to-material ratio is 1:10; Step 3, the tungsten-high entropy alloy co-laminated mixed powder obtained in step 2 is placed in a steel cold pressing mold for self-assembly, and then cold pressed for 60 seconds at a pressure of 20 MPa on a four-column hydraulic press to obtain a tungsten-AlNbTiV co-laminated cold pressed green body; Step 4: cold-press the tungsten-AlNbTiV co-laminated green body obtained in step 3 under a vacuum of not more than 10 -1 The material was heated to 1100°C at a heating rate of 100°C / min and sintered for 40 minutes in a vacuum hot pressing furnace at 4000 Pa. The pressing pressure during the sintering process was 30 MPa. The material was cooled in the furnace to obtain a tungsten-AlNbTiV micro-laminated composite material.
[0022] Example 6 Step 1, tungsten powder with an average particle size of 50 μm and dual-phase high entropy alloy powder AlNbTiV with an average particle size of 50 μm are respectively loaded into a stainless steel ball mill and ball milled at a speed of 1300 r / min for 4 hours, with a ball-to-material ratio of 50:1. Before ball milling, the stainless steel ball mill is first evacuated and then filled with argon. The vacuuming and argon filling operations are repeated three times to obtain tungsten flake powder and AlNbTiV flake powder, and the diameter to thickness ratio of the tungsten flake powder and the high entropy alloy flake powder are both ≥50; Among them, the discharge current during ball milling was 80 mA, the discharge voltage was 20 kV, and the discharge frequency was 7 kHz; Step 2, using the tungsten flaky powder and AlNbTiV flaky powder obtained in step 1 as raw material powders, mixing them in a V-type mixer at a speed of 100 r / min for 4 hours to obtain a tungsten-AlNbTiV co-flaky mixed powder; Among them, the mass percentage of tungsten flake powder is 70%, Al 19 Fe 20 Co 20 Ni 41 The mass percentage of the flake powder is 30%; Stainless steel grinding balls are added to the V-type mixer, and the ball-to-material ratio is 1:10; Step 3, the tungsten-high entropy alloy co-laminated mixed powder obtained in step 2 is placed in a steel cold pressing mold for self-assembly, and then cold pressed for 30 seconds at a pressure of 25 MPa on a four-column hydraulic press to obtain a tungsten-AlNbTiV co-laminated cold pressed green body; Step 4: cold-press the tungsten-AlNbTiV co-laminated green body obtained in step 3 under a vacuum of not more than 10 -1 The material was heated to 1400°C at a heating rate of 100°C / min and sintered for 20 minutes in a vacuum hot pressing furnace at 45 MPa. The material was cooled in the furnace to obtain a tungsten-AlNbTiV micro-laminated composite material.
[0023] Example 7 Step 1: prepare tungsten powder with an average particle size of 1 μm and dual-phase high entropy alloy powder FeCoNiCrAl 0.6 The tungsten flake powder and FeCoNiCrAl2O3 powder were respectively put into a stainless steel ball mill and ball milled at a speed of 900 r / min for 4 h. The ball-to-material ratio was 10:1. Before ball milling, the stainless steel ball mill was first evacuated and then filled with argon. The evacuation and argon filling operation were repeated three times to obtain tungsten flake powder and FeCoNiCrAl2O3 powder. 0.6 The diameter to thickness ratio of the flake powder, tungsten flake powder and high entropy alloy flake powder is ≥50; The discharge current during ball milling is 80 mA, the discharge voltage is 20 kV, and the discharge frequency is 8 kHz. Step 2: The tungsten flake powder obtained in step 1 and FeCoNiCrAl 0.6 The flake powder was used as raw material powder and mixed in a V-type mixer at a speed of 200 r / min for 1 h to obtain tungsten-FeCoNiCrAl 0.6 Co-laminated mixed powder; Among them, the mass percentage of tungsten flake powder is 80%, Al 19 Fe 20 Co 20 Ni 41 The mass percentage of the flake powder is 20%; Stainless steel grinding balls are added to the V-type mixer, and the ball-to-material ratio is 1:10; Step 3: The tungsten-high entropy alloy co-laminated mixed powder obtained in step 2 is placed in a steel cold pressing mold for self-assembly, and then cold pressed for 60 seconds at a pressure of 20 MPa on a four-column hydraulic press to obtain tungsten-FeCoNiCrAl 0.6 Cold pressing of green body with common laminae; Step 4: The tungsten obtained in step 3 is 0.6 The green body is cold pressed in a vacuum degree of no more than 10 -1 Pa vacuum hot pressing furnace at a heating rate of 100 ° C / min to 1000 ° C sintering for 60 min, the pressing pressure during the sintering process is 50 MPa, and the furnace is cooled to obtain tungsten-FeCoNiCrAl 0.6 Micro-laminated composites.
[0024] Depend on Figure 2 It can be seen that the tungsten-Al 19 Fe 20 Co 20 Ni 41 Composite powder, and then combine tungsten and high entropy alloy by pressing and sintering to obtain tungsten-Al 19 Fe 20 Co 20 Ni 41 Micro-laminated composites; Introducing dual-phase high entropy alloy powder Al 19 Fe 20 Co 20 Ni 41 Taking advantage of the low density and strong-toughness matching of high-entropy alloys, tungsten is combined with high-entropy alloys to improve the toughness without reducing the strength of the composite material. By designing a micro-laminated structure, when the material is subjected to load impact, the cracks deflect multiple times between layers during the fracture process, increasing the energy required for crack propagation and improving the material's impact resistance.
Claims
1. A method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder, characterized in that: Follow the steps below to implement it: Step 1, plasma ball milling tungsten powder and high entropy alloy powder respectively to obtain tungsten flake powder and high entropy alloy flake powder; Step 2, mixing the tungsten flaky powder and the high entropy alloy flaky powder obtained in step 1 in a V-type mixer to obtain a tungsten-high entropy alloy co-flaky mixed powder; Step 3, placing the tungsten-high entropy alloy co-laminated mixed powder obtained in step 2 into a steel cold pressing mold for self-assembly, and then cold pressing to obtain a tungsten-high entropy alloy co-laminated cold pressed green body; Step 4, hot pressing and sintering the tungsten-high entropy alloy co-laminated cold-pressed green body obtained in step 3 in a vacuum hot pressing furnace to obtain a tungsten-high entropy alloy micro-laminated composite material.
2. The method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder according to claim 1, characterized in that: In step 1, the average particle size of the tungsten powder is 1 μm to 50 μm, and the average particle size of the high entropy alloy powder is 10 μm to 50 μm.
3. The method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder according to claim 1, characterized in that: The specific process of step 1 is: tungsten powder and high entropy alloy powder are respectively loaded into a stainless steel ball mill for ball milling. Before ball milling, the stainless steel ball mill is first evacuated and then filled with argon. The evacuation and argon filling operations are repeated three times to obtain tungsten flake powder and high entropy alloy flake powder.
4. The method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder according to claim 3, characterized in that: The ball-to-material ratio is 10~50:1, the ball mill speed is 900r / min~1400r / min, and the ball mill time is 1h~4h.
5. The method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder according to claim 3, characterized in that: During the ball milling process, the discharge current was 80 mA, the discharge voltage was 20 kV, and the discharge frequency was 7 kHz ~ 9 kHz.
6. The method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder according to claim 1 or 3, characterized in that: The diameter-to-thickness ratios of the tungsten flaky powder and the high entropy alloy flaky powder are both ≥50.
7. The method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder according to claim 1, characterized in that: In step 2, the ball-to-material ratio during the mixing process is 1:10, the rotation speed is 100 r / min~200 r / min, and the ball milling time is 1h~4h.
8. The method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder according to claim 1, characterized in that: In step 2, the mass percentage of the tungsten lamellar powder is 50% to 90%, the mass percentage of the high entropy alloy lamellar powder is 10% to 50%, and the sum of the mass percentages of the two is 100%.
9. The method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder according to claim 1, characterized in that: In step 3, the cold pressing pressure is 15MP~25MPa, and the holding time is 30s~90s.
10. The method for preparing a tungsten-high entropy alloy micro-laminated composite material based on flaky powder according to claim 1, characterized in that: In step 4, the hot pressing sintering temperature is 1000°C to 1400°C, the holding time is 20min to 60min, the pressure is 30MPa to 60MPa, and the vacuum degree is not greater than 10 -1 Pa.